Strategi Promosi Destinasi Wisata Cibubur Garden Eat dan Play dalam Meningkatkan Kunjungan Wisatawan Melalui Instagram - Fitriya, Adinda; Kusumaningrum, Rastri; Mardiani Lubis, Flori (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
West Java has now become a very popular tourist destination, showing a significant increase in the number of visits. Data from the West Java Provincial Tourism and Culture Office recorded more than 22 million domestic tourists and 1,156 foreign tourists until the third quarter of 2022. A special focus on Bogor, one of the main destinations in West Java, shows its popularity among domestic tourists, especially at Bogor Botanical Gardens and Taman Safari. The importance of destination marketing, especially through social media, is recognized as a key factor in long-term tourism development. Therefore, research was conducted by adopting Regina Luttrell's concept entitled "Utilization of Instagram Social Media on @cibubur.garden Account as a Tourism Promotion Media." This research aims to analyze the promotional strategies carried out by Cibubur Garden through the Instagram account @cibubur.garden to increase the number of tourist visits. The research method used is a constructivist paradigm with a qualitative approach and descriptive research design. The main data was obtained through interviews with related parties of Cibubur Garden and direct observation of promotional activities through Instagram @cibubur.garden. The results show that Cibubur Garden Eat & Play successfully utilizes Instagram as the main tool in promoting its tourist destination. Instagram content involves the use of various features such as feeds, reels, and stories to maximize interaction and engagement with followers. This promotional strategy achieves the stages in the AIDA model (Attention, Interest, Desire, Action).